Perception of Type 2 Diabetes Mellitus Patient About Diabetic Wound Prevention - Mohamad Roni Alfaqih; Bayu Akbar K; Adhe Anisa P (poltekkes kemenkes mataram, 2021)
The prevalence of diabetes mellitus increases every year, this case make the risk of diabetes complications increase. One of the complication is diabetic wound.The prevention of wound is needed to avoid diabetic wound. The purpose of this study was to explore the perceptions of diabetics about prevention of diabetic wounds in patients. This study design used a qualitative research with phenomenology approach. Data collection used in-depth interview method that involving five participants. The results of this study got 18 themes with a large theme, that is hoping to be able for carry out prevention activities properly so that injuries do not occur. The conclusion of this study is that diabetes mellitus sufferers realize that diabetes is a disease that can makes unstable blood sugar and is caused by poor lifestyle, Patients know that diabetic wounds can occur on himself, so diabetes mellitus suffer take preventive measures such as wearing footwear and be careful in daily activity, do sports activities and avoid places that has risk and handle injuries immediately. This is meassure because the participants are afraid that if there is a diabetic wound on him self, then the participants hope to avoid diabetic wounds with proper prevention.